The equation of the line passing through the points (x1, y1) and (x2, y2) is given by ( y - y1) = [( y2 - y1)/(x2 - x1)]( x - x1)

As the line passes through ( -1 , 3) and (3 , 1) we can substitute the values we have to get :

( y - 3) = [( 1 - 3)/(3 + 1)]( x + 1)

=> 4( y - 3) = -2( x + 1)

=> 2y - 6 = -x - 1

=> 2y = -x + 5

=> y = -x/2 + 5/2

=> f(x) = -x/2 + 5/2

**The required function is f(x)= -x/2 + 5/2**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.